Modeling salinity risk response to irrigation practices for cotton production under film mulched drip irrigation in Xinjiang - Songrui Ning; An Yan; Beibei Zhou; Quanjiu Wang (Water Supply, 2022)
Predicting the impacts of the irrigation amount (IA), water salinity (WS), and antecedent soil salinity (AS) on soil salinization, the crop yield, and water productivities (WPs) are important for precision agriculture. We used a calibrated HYDRUS − 2D model coupled with a validated crop water production function to quantitatively determine the response of a soil − cotton system to three factors (IA, WS, and AS) in 30 scenarios under film mulched drip irrigation. These scenarios included five IAs, two ASs, and three WSs. Under the same IA and WS, the transpiration, evapotranspiration, yield, and WPs were lower, whereas the evaporation, drainage, soil water storage, and leached salt were higher under higher AS (over the salt tolerance threshold of cotton) scenarios. Under lower AS scenarios, desalination processes (20.2 to 166.8 g m−2) occurred in freshwater (0.38 dS m−1) irrigation scenarios and salt accumulated (425.8 to 1,442.4 g m−2) in saline water (3.10 and 7.42 dS m−1) irrigation scenarios. Desalination processes (2,273.4 to 4,692 g m−2) occurred in the higher AS scenarios. Salinity risk warning should be the focus for cotton fields with lower AS and saline water irrigation. Our results may help to identify the salinity risk to support sustainable cotton production in Xinjiang. HIGHLIGHTS Desalination occurred in cotton fields under higher soil salinity scenarios.; Cotton fields with lower antecedent soil salinity and irrigated saline water poses a salinity risk.; Water/salt balance components, yield, and water productivities functions of irrigation amount and water salinity.;